ACQUISITION OF ROAD SPECTRUM BASED ON FEMFAT LAB-ADAMS - FENG JinZhi; ZHENG GuangLei; ZHENG SongLin; ZHAO LiHui; LIANG JunYi (Jixie qiangdu)
The development of virtual prototype technology makes the vehicle multi-bod dynamics simulation and virtual fatigue durability calculation become the necessary means of engineering research,and obtaining reliable and effective road spectrum is the premise of the two means. This paper build road spectrum solution joint simulation platform based on FEMFAT LAB-ADAMS,and the response channel is established on the multi-body dynamics model according to the installation position of the actual vehicle sensor. The road spectrum is calculated based on the virtual iteration theory and the real road spectrum of the engine connection point and the shock absorber mounting point. The reliability of the road spectrum solution is verified by comparing the monitoring signal and the measured signal from three aspects of time domain characteristics,frequency domain characteristics and damage calculation. The results show that the reliable road spectrum can be used for vehicle multi-body dynamics simulation and virtual fatigue durability calculation.